EFFECTIVENESS GUIDED INQUIRY LEARNING METHOD TOWARDS SCIENCE LEARNING OUTCOMES OF FOURTH GRADE HIGH ACHIEVING STUDENTS ON THEME 8 AT SD 1 TRIRENGGO - Tri Avivah Kusuma Dewi; Rochmat Wahab (Universitas Negeri Yogyakarta, 2019)
This study attemps to know the effectiveness guided inquiry learning method towards science learning outcomes of fourth grade high achieving students on theme 8 at SD 1 Trirenggo. The study use a kind of quasi experiment with a quantitative approch with one group pretest and posttest design. The subject were 4 high achieving students of fourth grade at SD 1 Trirenggo. The technique of data collection use a test, observation, and documentation. Data analysis in this study with quantitative decription statistic. The result of this study indicates the increased value posttest that having given guided inquiry learning method treatment. The result of each subject in increasing on the subject ALF increased of 65 be 80 with a good criteria, subjek FDL increased value of 55 be 75 with enough criteria, subjek MYL increased value of 75 be 85 with good criteria, and subject SFD increased value of 60 be 80 with good criteria. The increase shows that guided inquiry learning method effective againts the science learning outcomes of fourth grade high achieving students on theme 8 at SD 1 Trirenggo